Two episodes of Stenotrophomonas maltophilia endocarditis of prosthetic mitral valve: report of a case and review of the literature. - Kim, Jae-Han (Korean Academy of Medical Sciences, 2002)
Stenotrophomonas maltophilia (previously named Xanthomonas maltophilia) is an aerobic, non-fermentive, Gram-negative bacillus that is wide spread in the environment. It was considered to be an organism with limited pathogenic potential, which was rarely capable of causing diseases in human other than those who were in debilitated or immunocompromised state. More recent studies have established that Stenotrophomonas maltophilia can behave as a true pathogen. Endocarditis due to this organism is rare, and only 24 cases of Stenotrophomonas maltophilia endocarditis have been reported in the medical literature. Most cases were associated with risk factors, including intravenous drug abuse, dental treatment, infected intravenous devices, and previous cardiac surgery. We present a case with two episodes of Stenotrophomonas maltophilia endocarditis after mitral valve prosthesis implantation, which was treated with antibiotics initially, and a combination of antibiotics and surgery later. To our knowledge, this is the first case of repetitive endocarditis due to Stenotrophomonas maltophilia.